COMPARATIVE STUDY BETWEEN BLADDER DIARY AND URODYNAMIC STUDY TO IDENTIFY LOWER URINARY TRACT SYMPTOMS: ESTUDIO COMPARATIVO ENTRE EL DIARIO VESICAL Y EL ESTUDIO URODINÁMICO PARA IDENTIFICAR LOS SÍNTOMAS DEL TRACTO URINARIO INFERIOR (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To identify the similarity of lower urinary tract symptoms presented in the urodynamic study compared to the urinary diary. Method: This is a comparative study carried out in an urodynamics clinic in southern Santa Catarina, Brazil, with 44 patients who underwent the examination. Data collection was carried out by applying a questionnaire and a 72-hour bladder diary and comparing it with the findings of the urodynamic study using the SPSS for Windows and Stata/SE v.14.1 programs. Results: The bladder diary showed high specificity, sensitivity, and accuracy for identifying detrusor hyperactivity and stress urinary incontinence. There was no difference for bladder capacity (p* 0.198). It pointed to bladder sensitivity with a volume smaller than that presented by the urodynamic study (p*